2022
DOI: 10.1126/science.abo2196
|View full text |Cite
|
Sign up to set email alerts
|

Aqueously altered igneous rocks sampled on the floor of Jezero crater, Mars

Abstract: The Perseverance rover landed in Jezero crater, Mars, to investigate ancient lake and river deposits. We report observations of the crater floor, below the crater’s sedimentary delta, finding the floor consists of igneous rocks altered by water. The lowest exposed unit, informally named Séítah, is a coarsely crystalline olivine-rich rock, which accumulated at the base of a magma body. Fe-Mg carbonates along grain boundaries indicate reactions with CO 2 -rich water, under water-poor cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
178
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(209 citation statements)
references
References 82 publications
13
178
0
Order By: Relevance
“…Our identifications of olivine and pyroxene minerals are supported by stoichiometric analysis of the PIXL data and are consistent with observations by other Perseverance instruments ( 5 ). We found that the beige equant grains have molar (Mg+Fe)/Si ≈ 2 and total cations of 2.995 to 3.025 per four oxygens (table S2), which is consistent with olivine’s chemical formula, (FeMg) 2 SiO 4 .…”
Section: Pixl Observationssupporting
confidence: 90%
See 4 more Smart Citations
“…Our identifications of olivine and pyroxene minerals are supported by stoichiometric analysis of the PIXL data and are consistent with observations by other Perseverance instruments ( 5 ). We found that the beige equant grains have molar (Mg+Fe)/Si ≈ 2 and total cations of 2.995 to 3.025 per four oxygens (table S2), which is consistent with olivine’s chemical formula, (FeMg) 2 SiO 4 .…”
Section: Pixl Observationssupporting
confidence: 90%
“…The intergrain reddish-brown materials contain silicates, Fe–Mg carbonate, and Fe–Mg–Ca sulfate, which are secondary materials from alteration. The presence of carbonates was also indicated by other instruments on Perseverance ( 5 ) and consistent with orbital observations. We focused our analysis on the primary minerals.…”
Section: Pixl Observationssupporting
confidence: 88%
See 3 more Smart Citations